2023
DOI: 10.1177/26318318231181689
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression and its Predictors among International Postgraduate Students Studying Public Health at a UK University

Hanieh Hosseinpur,
Ali Davod Parsa,
Russell Kabir

Abstract: Objective: This study examined the prevalence and existing predictors of depression in international postgraduate public health students at a university in England. Material and Methods: It was carried out as a descriptive cross-sectional survey. A total of 153 students enrolled in MSc in public health and community well-being and MPH in global public health courses were recruited using a convenience sampling technique. The Centre for Epidemiological Studies Depression 10-Item Scale (CES-D-10) and Chi-squared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A 2022 survey assessing the mental health of nearly 80,000 college students in China revealed a depression risk detection rate of approximately 21.48%. Similarly, a 2021 survey in England reported that 37% of undergraduate students were experiencing major depressive symptoms, and a study focusing on international postgraduate students studying public health at a university found a depression prevalence of 34.6% ( 3 , 4 ). Depression can have a profound impact on various aspects of life, including relationships with family, friends, and community.…”
Section: Introductionmentioning
confidence: 99%
“…A 2022 survey assessing the mental health of nearly 80,000 college students in China revealed a depression risk detection rate of approximately 21.48%. Similarly, a 2021 survey in England reported that 37% of undergraduate students were experiencing major depressive symptoms, and a study focusing on international postgraduate students studying public health at a university found a depression prevalence of 34.6% ( 3 , 4 ). Depression can have a profound impact on various aspects of life, including relationships with family, friends, and community.…”
Section: Introductionmentioning
confidence: 99%